Awareness and Perception of Hepatitis C Self-Testing in Nigeria: A National Survey of Stakeholders and the Public - Victor Abiola Adepoju; Donald Chinazor Udah; Chinonye Alioha Ezenwa; Jamiu Ganiyu; Qorinah Estiningtyas Sakilah Adnani (Venereology)
Background: Hepatitis C virus (HCV) infection presents a significant public health challenge globally, particularly in high-burden countries like Nigeria, where an estimated 2.4 million individuals are living with HCV. HCV self-testing (HCVST) can potentially bridge the significant diagnosis gap and help individuals to determine their HCV status in the privacy of their homes. It offers a solution to overcome barriers related to stigma and limited access to healthcare. In Nigeria, Self-testing for hepatitis C has only been implemented in a pilot research context. This study aimed to assess stakeholder and community awareness and perceptions of HCVST in Nigeria. The findings will provide insights that could inform effective policies and future scale-up programs for HCV control. Methods: A cross-sectional descriptive study was conducted using an online social media survey administered through SurveyMonkey. The survey was disseminated across social media platforms and groups between October–November 2023. Participants included Nigerians (both health professionals and non-health professionals) aged 18 years or older residing in any of the 36 states and the Federal Capital Territory (FCT). Data collected include sociodemographic characteristics, awareness and perceptions of HCVST, and perceived benefits and barriers. Results: Of 321 respondents, 94% perceived HCVST as highly important. While 77% of respondents knew about HIVST, only 58% had prior knowledge of HCVST. The analysis also showed that healthcare workers had greater awareness of HIV self-testing (82.3%) compared to non-healthcare workers (50.0%). Most respondents (88%) were highly likely to recommend HCVST and perceived it as a cost-effective alternative to traditional testing. Key perceived benefits included increased disease detection and control (67%), improved access to testing (21%), and reduced stigma (11%). In the unadjusted model, geographical zone (Southern Nigeria: cOR = 0.49, 95% CI: 0.30–0.77, p = 0.002), work experience (more than 20 years: cOR = 2.79, 95% CI: 1.11–8.07, p = 0.039), and prior awareness of HIV self-testing (cOR = 5.24, 95% CI: 3.00–9.43, p < 0.001) were significant predictors of HCVST awareness. However, in the adjusted model, only prior awareness of HIV self-testing remained significant (aOR = 4.77, 95% CI: 2.62–8.94, p < 0.001). Conclusions: The strong support for HCVST among stakeholders in Nigeria highlights its potential to enhance HCV control, especially within the broader context of infectious diseases like STIs. The greater awareness of HIV self-testing among healthcare workers compared to non-healthcare workers indicates the need for targeted awareness campaigns for non-healthcare populations. Addressing these awareness gaps, leveraging lessons from HIVST, and using existing infrastructure will be crucial. Prioritizing public education, outreach, and effective linkage to care will drive the impact of HCVST in achieving HCV elimination goals and position it as a model for expanding similar STI interventions in Nigeria.